2016
DOI: 10.1140/epjc/s10052-016-4570-2
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and performance study of six-gap glass MRPC detectors

Abstract: The multigap resistive plate chambers (MRPCs) are gas ionization detectors with multiple gas sub-gaps made of resistive electrodes. The high voltage (HV) is applied on the outer surfaces of outermost resistive plates only, while the interior plates are left electrically floating. The presence of multiple narrow sub-gaps with high electric field results in faster signals on the outer electrodes, thus improving the detector's time resolution. Due to their excellent performance and relatively low cost, the MRPC d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, the spacers were small circular disks instead of fishing wires. Test results for this detector did not show a working point shift [11].…”
Section: Jinst 14 P01003mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the spacers were small circular disks instead of fishing wires. Test results for this detector did not show a working point shift [11].…”
Section: Jinst 14 P01003mentioning
confidence: 81%
“…The time resolution measured with the standard gas mixture is about 66 ps and it is better than the one measured with no SF 6 whose value is about 74 ps. This is the result of two competing processes [11]. The reduction of SF 6 will promote growth of the avalanche and results in a better time resolution and a lower working point.…”
Section: Jinst 14 P01003mentioning
confidence: 99%
“…The calibration is done using the equation 2. Efficiency study of our detector for cosmic muons can be found in [5]. MRPCs have very low efficiency for gammas.…”
Section: Time Resolution For 511 Kev Gammasmentioning
confidence: 99%
“…These detectors have been tested for their long time operation and we have achieved a time resolution of about 220 ps for cosmic muons. A detailed study of the detector characterization and it's performance can be found in [8]. We attempt to use these detectors for possible application in medical imaging because of their excellent time resolution.…”
Section: Introductionmentioning
confidence: 99%